A Comparative Analysis of Renewable Energy Use and Policies: Global and Turkish Perspectives - SELAM, AYŞE AYÇİM; ARIOĞLU, MAHMURE ÖVÜL; ER, MERVE; ÖZEL, SEMİH; FIRAT, SENİYE ÜMİT (MDPI AG, 2015)
The utilization of renewable energy sources (RES) has become inevitable, not only due to the increasing scarcity of fossil fuels, but also to sustain life on Earth. Consequently, countries have started developing renewable energy policies individually and as part of global organizations and networks, such as the Organization for Economic Co-operation and Development (OECD), the European Union (EU) and the International Energy Agency (IEA). Turkey is a developing OECD member country and in the accession process to the EU. Thus, the renewable energy policies should be aligned with those of the EU. Moreover, despite the substantial amount and wide range of RES, it is still in a position to import more than half of its energy demand. In the light of these facts, this study aims to analyze and compare the renewable energy policies in Turkey with those adopted worldwide to lay out possible solutions regarding its energy problems.
Keywords: renewable energy; renewable energy policies; renewable energy use; energy policy; Turkey; ELECTRICITY-GENERATION; UNITED-STATES; TURKEY; STRATEGIES; GERMANY; INSTRUMENTS; HYDROPOWER; DEPLOYMENT; COUNTRIES; MODEL